2011
DOI: 10.1002/bit.23294
|View full text |Cite
|
Sign up to set email alerts
|

Application of a novel thermostable NAD(P)H oxidase from hyperthermophilic archaeon for the regeneration of both NAD+ and NADP+

Abstract: A novel thermostable NAD(P)H oxidase from the hyperthermophilic archaeon Thermococcus kodakarensis KOD1 (TkNOX) catalyzes oxidation of NADH and NADPH with oxygen from atmospheric air as an electron acceptor. Although the optimal temperature of TkNOX is >90°C, it also shows activity at 30°C. This enzyme was used for the regeneration of both NADP(+) and NAD(+) in alcohol dehydrogenase (ADH)-catalyzed enantioselective oxidation of racemic 1-phenylethanol. NADP(+) regeneration at 30°C was performed by TkNOX couple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…The reactions were carried out at 50°C for 3 h in a capped 15-ml tube with shaking at a rate of 150 strokes · min Ϫ1 . The (R)-and (S)-1-phenylethanol remaining after the reaction was quantified by high-performance liquid chromatography (HPLC) as described previously (36). One unit of ADH activity corresponds to the oxidation of 1 mol (RS)-1-phenylethanol per minute.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reactions were carried out at 50°C for 3 h in a capped 15-ml tube with shaking at a rate of 150 strokes · min Ϫ1 . The (R)-and (S)-1-phenylethanol remaining after the reaction was quantified by high-performance liquid chromatography (HPLC) as described previously (36). One unit of ADH activity corresponds to the oxidation of 1 mol (RS)-1-phenylethanol per minute.…”
Section: Methodsmentioning
confidence: 99%
“…The activity of the native TkADH at each purification step was assayed by determining the consumption of (RS)-1-phenylethanol in the cofactor-regenerating reaction system with thermostable NAD(P)H oxidase from T. kodakarensis (TkNOX) (36). The reaction mixture was composed of 50 mM Tris-HCl buffer (pH 8.5), 20 mM (RS)-1-phenylethanol, 2 mM NAD(P) ϩ , 0.17 mM flavin adenine dinucleotide (FAD), 0.36 U · ml Ϫ1 of TkNOX, and an appropriate amount of the native TkADH in a total volume of 0.6 ml.…”
Section: Methodsmentioning
confidence: 99%
“…A drawback in using NADH oxidases for cofactor regeneration is that almost all water-forming NADH oxidases are specific for NADH. In wild type form only two water forming NOXs and one hydrogen peroxide forming NOX show activity with NADPH (around half / one third of activity with NADH depending on the NOX [38, 49, 50]. NOX 1299 from T. kodakarensis is the only NOX showing higher wild type activity with NADPH than with NADH but disadvantageously it produces high amounts of H 2 O 2 [45].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study had also revealed the high dependence of DavD (or GabD) on its cofactor, NAD(P) + (Hong et al, ). However, the high cost of NAD(P) + remained a limitation in the production of glutaric acid (Wu et al, ).…”
Section: Introductionmentioning
confidence: 99%